(3GdJPcQI aj Yde GdcdGes - (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3GdeTgO GdebOSi s)
(3ChdgG (B:s
(3Chd GdehLhO HPdc Cf jYQa GdGfSGf Cf dg hdLjeY GdYGde NGdbkG hCfg Mi bOGQ Ydi eGdGfgGjI dg s
(3BNQgG (B:s
(3aGddg JYGdi jLQi ddYdeGA NHQ Ch jQMe eG Vjge hjhab ef Hbi efge deG jQVjg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs